2021
DOI: 10.5194/adgeo-52-131-2021
|View full text |Cite
|
Sign up to set email alerts
|

GIS applications in volcano monitoring: the study of seismic swarms at the Campi Flegrei volcanic complex, Italy

Abstract: Abstract. Campi Flegrei caldera (Southern Italy) is one of the most hazardous volcanic complexes in the world since it is located inside the densely inhabited urban district of Naples-Pozzuoli. In the past, the caldera has produced devastating to moderate eruptions and periodically undergoes from strong to minor uplift episodes, named “bradyseism”, almost always accompanied by seismic swarms. Starting from 2005 Campi Flegrei has undergone an unrest crisis, characterized by ground uplift, localized gas emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…The work of Berrino and Ricciardi (2020) presented the results of several absolute gravity measurements carried out at the Campi Flegrei active caldera (Italy) over a dense absolute gravity network. The latter was established in 2015, permitting an advanced approach for volcano monitoring.…”
Section: Contributions To the Special Volumementioning
confidence: 99%
See 1 more Smart Citation
“…The work of Berrino and Ricciardi (2020) presented the results of several absolute gravity measurements carried out at the Campi Flegrei active caldera (Italy) over a dense absolute gravity network. The latter was established in 2015, permitting an advanced approach for volcano monitoring.…”
Section: Contributions To the Special Volumementioning
confidence: 99%
“…The work of Bellucci Sessa et al (2021) showed the ability of GIS (Geographical Information System) to manage a great quantity of data. Two GIS technology applications, based on the seismic catalogue of Campi Flegrei (Italy) from 2005 to 2019 were shown, in addition to the creation of a new Geo-Database.…”
Section: Contributions To the Special Volumementioning
confidence: 99%
“…2b). Here, shear-wave-splitting anisotropy 39 , InSAR 11 , and gravity gradiometry 33 identify a SN anomaly that accumulates the highest lateral stress during unrest 10 , producing small-magnitude earthquakes 31 (Fig 2b,diamonds).…”
mentioning
confidence: 91%
“…The azimuth of the horizontal polarization vector derived from ambient noise and the resultant length of its distribution (R) 1,2,29,30 are used here for the rst time as both imaging and diagnostic tools (Methods, 0.2-1 Hz). During periods of low seismic release 31,32 , they detect the hypothesized link between deep extensional and caldera-bounding faults (extensional structures) that bear regional stress [33][34][35][36][37] north and east of the caldera (Fig. 1a, white dotted line), and a dynamic transfer…”
mentioning
confidence: 99%
See 1 more Smart Citation